Non-invasive quantification of right ventricular systolic function by echocardiography: a new semi-automated approach - Greiner, Sebastian; André, Florian; Heß, Alexander; Steen, Henning; Katus, Hugo; Mereles, Derliz (Clinical research in cardiology, 2013)
BackgroundRight ventricular (RV) function determines long-term outcome in many cardiopulmonary diseases. However, the assessment of RV function is time-consuming and surrogate parameters derived from two-dimensional (2D) or Doppler echocardiography show poor consistency.MethodsForty consecutive patients were examined within 30 min after magnetic resonance imaging (MRI) with comprehensive echocardiography, including strain imaging and real-time three-dimensional echocardiography. A new parameter, the RV automated systolic index (RV-ASI), was obtained from the apical four-chamber view using semi-automated border detection.ResultsRV-ASI could be assessed by 2D echocardiography in 38 of 40 patients. RV ejection fraction assessed by MRI was 48 ± 9 %, while RV-ASI was 52 ± 11 % (r = 0.74, SEE = 6 %, p < 0.0001). Intra- and inter-observer variabilities were 7.5 and 8.9 %, respectively. An RV-ASI cut-off value of 52 % in this cohort was able to differentiate between normal and impaired RV function (AUC 0.92, sensitivity 87 %, specificity 93 %).ConclusionsIn this study, the RV-ASI showed to be an easy, rapid to assess and reliable tool for quantification of right ventricular function. Furthermore, this index can complement the assessment of right ventricular mechanics by 2D strain imaging for efficient and comprehensive non-invasive evaluation of right ventricular function.